A hard alloy with a metal ceramic layer on the surface and a preparation method thereof
By forming a cermet layer on the surface of the cemented carbide, and using laser cladding technology to combine wear-resistant phase, transition phase and toughening matrix, the problem of reduced performance of cemented carbide at high temperatures is solved, and the high hardness, wear resistance and toughness of cemented carbide is achieved, and its application breadth is improved.
Patent Information
- Application Number
- CN202411837203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-08
AI Technical Summary
The existing cemented carbide has significantly reduced flexural strength, hardness and other properties in high temperature environments, and it is difficult to have good toughness, wear resistance and hardness at the same time, which limits its wide application.
A cemented carbide design with a surface layer of cermet layer, including a cemented carbide layer and a metal cermet layer. The cermet layer consists of a wear-resistant phase (such as diamond, B4C or SiC), a transition phase (such as TiC, W or WC) and a toughened matrix (such as Co, Fe or Ni). The composite coating is formed through laser cladding technology to enhance the surface performance of the cemented carbide.
The high hardness and wear resistance of the surface layer of cemented carbide is achieved, while the toughness of the core layer is maintained, significantly improving the high-temperature service life and overall performance of cemented carbide.
Smart Images

Figure CN119776710A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cemented carbide, and in particular to a cemented carbide with a metal ceramic layer on the surface and a preparation method thereof. Background Art
[0002] Cemented carbide is an alloy material made of hard compounds of refractory metals and bonding metals through powder metallurgy. Due to its high hardness, wear resistance, good strength and toughness, heat resistance, corrosion resistance and other excellent properties, cemented carbide is widely used in military industry, aerospace, mechanical processing, metallurgy, oil drilling, mining tools, electronic communications, construction and other fields. Most of the existing cemented carbides are based on Co, Ni, Fe single elements as bonding phase and WC as hard phase. Under high temperature environment (above 400℃), the bending strength, hardness and other properties are significantly reduced, and the high temperature service life is also significantly reduced.
[0003] Prior art CN105177388A discloses a cemented carbide material, which is composed of the following components in weight percentage: 1-20% of a binder phase, 80-99% of a hard phase, wherein the hard phase is composed of WC and TiAlCN, wherein the weight percentage of WC in the cemented carbide material is 60-98.5%, and the weight percentage of TiAlCN in the cemented carbide material is 0.5-20%. The cemented carbide can make the hard phase have higher hardness and oxidation resistance, and can improve the high temperature strength, hardness and toughness of the prepared cemented carbide tool, thereby improving the high temperature service life of the cemented carbide.
[0004] However, the above-mentioned cemented carbide cannot have good toughness, wear resistance and hardness at the same time, thus limiting the wide application of cemented carbide. Summary of the invention
[0005] The purpose of the present invention is to provide a cemented carbide with a metal ceramic layer on the surface and a preparation method thereof, so as to solve the technical problem that the existing cemented carbide cannot have good toughness, wear resistance and hardness at the same time, thus limiting the wide application of cemented carbide.
[0006] To achieve the above-mentioned objectives, in a first aspect, the present invention provides a cemented carbide having a surface layer as a metal ceramic layer, the cemented carbide comprising a surface layer and a core layer, the surface layer being a metal ceramic layer, the core layer being a cemented carbide layer, the cemented carbide layer being a WC-Co cemented carbide layer, the metal ceramic layer comprising a wear-resistant phase, a transition phase and a toughening matrix, the transition phase being coated on the surface of the wear-resistant phase, and the toughening matrix being coated on the surface of the transition phase; the wear-resistant phase is one or more of diamond, B4C or SiC; the transition phase is one or more of TiC, W or WC; the toughening matrix is one or more of Co, Fe or Ni.
[0007] Wherein, the volume ratio of the wear-resistant phase, the transition phase and the toughening matrix is (30-80): (20-50): (10-40).
[0008] The mass content of Co in the WC-Co hard alloy layer is 5-35%, and the rest is WC.
[0009] The cemented carbide is coated with a composite coating having an inner coating of Al203-TiN and an outer coating of TiCN.
[0010] In a second aspect, the present invention further provides a method for preparing a cemented carbide having a surface layer as a metal ceramic layer, comprising the following steps:
[0011] Selecting appropriate amounts of WC and Co as raw materials, heating the WC and Co until they are completely dissolved, mixing them, spreading them flat and solidifying them to form a cemented carbide layer;
[0012] Selecting an appropriate amount of one or more of diamond, B4C or SiC as wear-resistant phase raw materials, sintering and melting the wear-resistant phase raw materials until a solution is completely formed, and then mixing and flattening the wear-resistant phase raw materials to solidify to form a first outer layer;
[0013] Selecting an appropriate amount of one or more of TiC, W or WC as a transition phase raw material, and evenly spreading the transition phase raw material outside the first outer layer;
[0014] Scanning the first outer layer according to the preset cross-sectional profile of the first outer layer using a laser beam, so that the transition phase raw material is sintered outside the first outer layer to form a second outer layer;
[0015] Selecting an appropriate amount of one or more of Co, Fe or Ni as a toughening matrix raw material, and evenly spreading the toughening matrix raw material outside the second outer layer;
[0016] Scanning the second outer layer according to the preset cross-sectional profile of the second outer layer again by using the laser beam to sinter the toughened matrix material outside the second outer layer to form a third outer layer;
[0017] The third outer layer is placed outside the upper and lower layers of the hard alloy layer, and the third outer layer is sintered and melted until the third outer layer is completely attached to the outside of the hard alloy layer to obtain the desired hard alloy.
[0018] When a laser beam is used, the power of the laser beam is 300-500W, the spot diameter is 30-200μm, the scanning interval is 0.05-0.07mm, the scanning speed is 800-1600mm / s, and the energy density reaches 106-125W / cm 2.
[0019] After the hard alloy is prepared, a composite coating having an inner coating of Al203-TiN and an outer coating of TiCN is coated on the outside of the hard alloy to further improve the wear resistance and toughness of the hard alloy.
[0020] The present invention discloses a cemented carbide with a surface layer being a metal ceramic layer and a preparation method thereof. The surface layer of the cemented carbide is a metal ceramic layer, the core layer is a WC-Co cemented carbide layer, the transition phase of the metal ceramic layer is coated on the surface of the wear-resistant phase, and the toughening matrix is coated on the surface of the transition phase. Since the Co-based alloy has good wear resistance and Co has good fluidity and can melt carbides, super-hard ceramic particles with high melting points such as TiC, B4C, and SiC are added to Co. The composite coating formed after laser cladding matches the main hardness, and the hardness and wear resistance of the cladding layer can be significantly improved, so that the surface layer of the cemented carbide has high hardness and wear resistance, and at the same time, the core layer has good toughness, which solves the technical problem that the existing cemented carbide cannot have good toughness, wear resistance and hardness at the same time, thereby limiting the wide application of cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0022] Figure 1 It is a schematic structural diagram of a cemented carbide having a surface layer of a metal ceramic layer in the first embodiment of the present invention.
[0023] Figure 2 It is a process step diagram of a method for preparing a cemented carbide having a metal ceramic layer as a surface layer according to a second embodiment of the present invention.
[0024] In the figure: 101 - core layer, 102 - wear-resistant phase, 103 - transition phase, 104 - toughening matrix, 105 - composite coating. DETAILED DESCRIPTION
[0025] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0026] First embodiment:
[0027] See also Figure 1 The present invention provides a cemented carbide having a surface layer as a metal ceramic layer, wherein the cemented carbide comprises a surface layer and a core layer 101, wherein the surface layer is the metal ceramic layer, and the core layer 101 is a cemented carbide layer.
[0028] In this embodiment, the surface layer of the cemented carbide used in the present invention is a metal ceramic layer, the core layer 101 is a cemented carbide layer, the transition phase 103 of the metal ceramic layer is coated on the surface of the wear-resistant phase 102, and the toughening matrix 104 is coated on the surface of the transition phase 103. Since the Co-based alloy has good wear resistance, and Co has good fluidity and can melt carbides, high-melting-point superhard ceramic particles such as TiC, B4C, and SiC are added to Co. The composite coating 105 formed after laser cladding matches the hardness of the main body, which can significantly improve the hardness and wear resistance of the cladding layer, so that the surface layer of the cemented carbide has high hardness and wear resistance, and at the same time, the core layer 101 has good toughness.
[0029] Among them, the cemented carbide layer is a WC-Co cemented carbide layer, the metal ceramic layer includes a wear-resistant phase 102, a transition phase 103 and a toughening matrix 104, the transition phase 103 is coated on the surface of the wear-resistant phase 102, and the toughening matrix 104 is coated on the surface of the transition phase 103; the wear-resistant phase 102 is one or more of diamond, B4C or SiC; the transition phase 103 is one or more of TiC, W or WC; the toughening matrix 104 is one or more of Co, Fe or Ni.
[0030] Secondly, in the WC-Co cemented carbide layer, the particle size of WC is 20-800nm, and the particle size of Co is 100-500nm.
[0031] Again, the particle size of the metal or metal compound particles in the metal ceramic layer is 30-200 μm.
[0032] Meanwhile, the volume ratio of the wear-resistant phase 102, the transition phase 103 and the toughening matrix 104 is (30-80): (20-50): (10-40).
[0033] In addition, the mass content of Co in the WC-Co hard alloy layer is 5-35%, and the rest is WC.
[0034] Finally, the cemented carbide is coated with a composite coating 105 with an inner coating of Al203-TiN and an outer coating of TiCN.
[0035] When a cemented carbide having a surface layer of a metal ceramic layer is used in the present embodiment, the surface layer of the cemented carbide is a metal ceramic layer, the core layer 101 is a WC-Co cemented carbide layer, the transition phase 103 of the metal ceramic layer is coated on the surface of the wear-resistant phase 102, and the toughening matrix 104 is coated on the surface of the transition phase 103. Since the Co-based alloy has good wear resistance, and Co has good fluidity and can melt carbides, high-melting-point superhard ceramic particles such as TiC, B4C, and SiC are added to Co. The composite coating 105 formed after laser cladding matches the main hardness, which can significantly improve the hardness and wear resistance of the cladding layer, so that the surface layer of the cemented carbide has high hardness and wear resistance. At the same time, the core layer 101 has good toughness, which solves the technical problem that the existing cemented carbide cannot have good toughness, wear resistance and hardness at the same time, thereby limiting the wide application of cemented carbide.
[0036] Second embodiment:
[0037] Based on the first embodiment, please refer to Figure 2 The present invention also provides a method for preparing a cemented carbide having a surface layer as a metal ceramic layer, comprising the following steps:
[0038] S101, selecting appropriate amounts of WC and Co as raw materials, heating the WC and Co until they are completely dissolved, mixing them, spreading them flat and solidifying them to form a cemented carbide layer.
[0039] Specifically, appropriate amounts of WC and Co are selected as raw materials, and the WC and Co are heated to completely form a solution, and then the formed WC solution and Co solution are mixed. After being evenly mixed, the mixed solution is flattened and solidified to form a cemented carbide layer, wherein the mass content of Co is 5-35%, and the rest is WC, the particle size of WC is 20-800nm, and the particle size of Co is 100-500nm.
[0040] S102, selecting an appropriate amount of one or more of diamond, B4C or SiC as the raw material of the wear-resistant phase 102, sintering and melting the raw material of the wear-resistant phase 102 until a solution is completely formed, and then mixing and flattening the raw material of the wear-resistant phase 102 to solidify to form a first outer layer.
[0041] Specifically, an appropriate amount of one or more of diamond, B4C or SiC is selected as the raw material of the wear-resistant phase 102, and the selected raw material of the wear-resistant phase 102 is sintered and melted until the raw material of the wear-resistant phase 102 completely forms a solution, and then the formed solution is mixed. After mixing evenly, the mixed solution is spread and solidified to form a first outer layer, wherein the particle size of diamond, B4C or SiC is 30-150μm.
[0042] S103, selecting an appropriate amount of one or more of TiC, W or WC as a raw material for the transition phase 103, and evenly spreading the raw material for the transition phase 103 outside the first outer layer.
[0043] Specifically, a proper amount of one or more of TiC, W or WC is selected as the raw material of the transition phase 103, and the selected raw material of the transition phase 103 is evenly spread outside the first outer layer, wherein the particle size of TiC, W or WC is 50-200 μm.
[0044] S104, using a laser beam to scan according to the preset cross-sectional profile of the first outer layer, so that the transition phase 103 raw material is sintered outside the first outer layer to form a second outer layer.
[0045] Specifically, a laser beam is used to scan according to the preset cross-sectional profile of the first outer layer, so that the transition phase 103 raw material is sintered outside the first outer layer to form a second outer layer. When a laser beam is used, the power of the laser beam is 300-400W, the spot diameter is 30-200μm, the scanning interval is 0.05-0.07mm, the scanning speed is 800-1600mm / s, and the energy density reaches 106-110W / cm 2 .
[0046] S105, selecting an appropriate amount of one or more of Co, Fe or Ni as a raw material for the toughening matrix 104, and evenly spreading the raw material for the toughening matrix 104 outside the second outer layer.
[0047] Specifically, a proper amount of one or more of Co, Fe or Ni is selected as the raw material of the toughening matrix 104, and the selected raw material of the toughening matrix 104 is evenly spread outside the second outer layer, wherein the particle size of Co, Fe or Ni is 40-180 μm.
[0048] S106, scanning again with the laser beam according to the preset cross-sectional profile of the second outer layer, so that the toughening matrix 104 raw material is sintered outside the second outer layer to form a third outer layer.
[0049] Specifically, a laser beam is used again to scan according to the preset cross-sectional profile of the second outer layer, so that the raw material of the toughening matrix 104 is sintered outside the second outer layer to form a third outer layer, wherein the first outer layer is the wear-resistant phase 102, the second outer layer is the transition phase 103, and the third outer layer is the toughening matrix 104. The volume ratio of the wear-resistant phase 102, the transition phase 103 and the toughening matrix 104 is (30-80): (20-50): (10-40). When a laser beam is used, the power of the laser beam is 400-500W, the spot diameter is 30-100μm, the scanning interval is 0.05-0.07mm, the scanning speed is 800-1500mm / s, and the energy density reaches 106-120W / cm 2 .
[0050] S107, placing the third outer layer outside the upper and lower layers of the cemented carbide layer, sintering and melting the third outer layer until the third outer layer is completely attached to the outside of the cemented carbide layer, and obtaining the desired cemented carbide.
[0051] Specifically, a third outer layer is placed outside the upper and lower layers of the cemented carbide layer, and the third outer layer is continuously sintered and melted using a laser beam until the third outer layer is completely attached to the outside of the cemented carbide layer. After solidification, the desired cemented carbide can be obtained. After the desired cemented carbide is prepared, it is necessary to coat the cemented carbide with a composite coating 105 having an inner coating of Al203-TiN and an outer coating of TiCN to further improve the wear resistance and toughness of the cemented carbide.
[0052] What is disclosed above is only one or more preferred embodiments of the present application, and cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A cemented carbide having a surface layer of a metal ceramic layer, the cemented carbide comprising a surface layer and a core layer, the surface layer being a metal ceramic layer, the core layer being a cemented carbide layer, characterized in that: The cemented carbide layer is a WC-Co cemented carbide layer, the metal ceramic layer comprises a wear-resistant phase, a transition phase and a toughening matrix, the transition phase is coated on the surface of the wear-resistant phase, and the toughening matrix is coated on the surface of the transition phase; The wear-resistant phase is one or more of diamond, B4C or SiC; The transition phase is one or more of TiC, W or WC; The toughening matrix is one or more of Co, Fe or Ni.
2. The hard alloy with a metal ceramic layer as the surface layer according to claim 1, characterized in that: The volume ratio of the wear-resistant phase, the transition phase and the toughening matrix is (30-80):(20-50):(10-40).
3. The hard alloy with a metal ceramic layer as the surface layer according to claim 1, characterized in that: The mass content of Co in the WC-Co hard alloy layer is 5-35%, and the rest is WC.
4. The hard alloy with a metal ceramic layer as the surface layer according to claim 1, characterized in that: The hard alloy is coated with a composite coating in which the inner coating is Al203-TiN and the outer coating is TiCN.
5. A method for preparing a cemented carbide having a metal-ceramic layer on the surface, applied to the cemented carbide having a metal-ceramic layer on the surface as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Selecting appropriate amounts of WC and Co as raw materials, heating the WC and Co until they are completely dissolved, mixing them, spreading them flat and solidifying them to form a cemented carbide layer; Selecting an appropriate amount of one or more of diamond, B4C or SiC as wear-resistant phase raw materials, sintering and melting the wear-resistant phase raw materials until a solution is completely formed, and then mixing and flattening the wear-resistant phase raw materials to solidify to form a first outer layer; Selecting an appropriate amount of one or more of TiC, W or WC as a transition phase raw material, and evenly spreading the transition phase raw material outside the first outer layer; Scanning the first outer layer according to the preset cross-sectional profile of the first outer layer using a laser beam, so that the transition phase raw material is sintered outside the first outer layer to form a second outer layer; Selecting an appropriate amount of one or more of Co, Fe or Ni as a toughening matrix raw material, and evenly spreading the toughening matrix raw material outside the second outer layer; The laser beam is used again to scan according to the preset cross-sectional profile of the second outer layer, so that the toughened matrix raw material is sintered outside the second outer layer to form a third outer layer; The third outer layer is placed outside the upper and lower layers of the hard alloy layer, and the third outer layer is sintered and melted until the third outer layer is completely attached to the outside of the hard alloy layer to obtain the desired hard alloy.
6. The method for preparing a cemented carbide having a metal ceramic layer as a surface layer according to claim 5, characterized in that: When using a laser beam, the power of the laser beam is 300-500W, the spot diameter is 30-200μm, the scanning interval is 0.05-0.07mm, the scanning speed is 800-1600mm / s, and the energy density reaches 106-125W / cm 2 .
7. The method for preparing a cemented carbide having a metal ceramic layer as a surface layer according to claim 5, characterized in that: After the hard alloy is prepared, a composite coating having an inner coating of Al203-TiN and an outer coating of TiCN is coated on the outside of the hard alloy to further improve the wear resistance and toughness of the hard alloy.
Citation Information
Patent Citations
Hard alloy material
CN105177388A